Design and development of portable pineapple peeler : an ergonomics approach - Ahmad Hisyam, Mohamad (2010)
This thesis is about designing a portable pineapple peeler using ergonomics approach in order to avoid or minimize the risk of developing Musculoskeletal Disorders (MSD) among workers in pineapple industry. The workers especially in the small and medium enterprise still use the manual technique to peel the pineapple. MSD happens due to the products or tools that is not ergonomics. Some of physical activity risk factors related to MSD are application of force, repetitive movement and awkward posture. Working tools that is not ergonomics combining with the physical activity will results in MSD to develop and resulting pain in a long term period. There are three objectives for this study. The first objective of this study is to design a portable pineapple peeler with ergonomics approach using SolidWorks. The second objective is to make a prototype of the designed pineapple peeler using Rapid Prototyping (RP) and the third objective is to simulate the designed pineapple peeler using Algor Simulation software. While performing this project, the exclusions and the things known but not attempted to solve are the developed pineapple peeler is only prototype and is not readily functional as a commercial product and the simulation of the pineapple peeler using Algor Simulation software is considered precise. In designing process, two designs with different handle diameter were developed using SolidWorks. The design with handle diameter of 50 mm has been named as Design A while the design with handle diameter of 38 mm has been named as Design B. The designs have been analyzed using Algor Simulation software to evaluate the force distribution on the critical part of the pineapple peeler when it is used by the workers. Based on the results of the simulation, both Design A and Design B can withstand the extended allowed number of force. However, Design A can withstand higher forces and provides higher level of safety to the user compared to Design B. Thus, the chance to prevent MSD from occurring by applying Design A is higher than Design B. In the end, it can be decided that Design A should be used in designing the portable pineapple peeler. The usage of ergonomics in producing a product will helps to save life. The MSD will affect people in long term period and before they know it, it has gotten worst. Thus, the designed pineapple peeler will minimize and reduce the risk of having MSD among workers in pineapple industry